ORGANIC LIVESTOCK DEVELOPMENT SHEEP - Rr. Herini Siti Aisyah; Epy M. Luqman (Jurnal Layanan Masyarakat (Journal of Public Services), 2017)
The farmers if the raising of cattle sheep capable of providing an income of 14–25% of the total income of farming families. Farmers’ income will increase if the intensively managed farm; and intensification will be successful if it is supported by the appropriate technology is adequate (simple but have a high eﬃciency). In these two villages there is some waste that can be used as animal feed ingredients such as rice straw, sugar cane leaves, leaves of corn, soybeans and others. Associated with the program in addressing the availability of food, the sheep will be done to empower farmers in the use of agricultural waste to be processed into animal feed is quite nutritious by administering probiotics. It is expected the farmers have no trouble feeding while maintaining sheep in large numbers, but it will also increase the eﬃciency of cost and time for farmers so that is expected to be a promising income for farmers. Expected to maintain sheep no longer a sideline but become a profession or occupation for farmers principal benefits are promising. AbstrakPetani penggemukan domba mampu memberikan pendapatan 14–25% dari total pendapatan keluarga. Pendapatan petani akan meningkat jika pertanian yang dikelola secara intensif; dan intensiﬁkasi akan berhasil jika didukung oleh teknologi yang tepat yang memadai (sederhana namun memiliki eﬁsiensi tinggi). Di kedua desa ini ada beberapa limbah yang bisa dijadikan bahan pakan ternak seperti jerami padi, daun tebu, daun jagung, kedelai dan lain-lain. Terkait dengan program dalam menangani ketersediaan makanan, domba-domba tersebut akan dilakukan untuk memberdayakan petani dalam penggunaan limbah pertanian untuk diolah menjadi pakan ternak yang cukup bergizi dengan pemberian probiotik. Diharapkan para petani tidak kesulitan memberi makan sambil memelihara domba dalam jumlah besar, namun juga akan meningkatkan eﬁsiensi biaya dan waktu bagi petani sehingga diharapkan bisa menjanjikan pendapatan bagi petani. Diharapkan untuk menjaga domba tidak lagi menjadi sampingan tapi menjadi profesi atau pekerjaan bagi tunjangan pokok petani yang menjanjikan.